BENTUK PENYAJIAN TOR-TOR DALAM UPACARA KEMATIAN SAUR MATUA PADA MASYARAKAT BATAK TOBA DI KECAMATAN PARSAORAN KOTA PEMATANG SIANTAR - Diana Diana; Darmawati Darmawati; Desfiarni Desfiarni (SENDRATASIK UNP, 2017)
AbstractThis research aims to find out and to describe the Tor-Tor dance in tradisional funeral ceremony saur matua in batak society at Pematang Siantar.This research was qualitative research. The object of the research was Tor-Tor dance in funeral ceremony in batak society at Pematang Siantar ciry. The instrument was the researcher herself with stationary,camera photo and handy camera. The data of this research were primary and secondary data. The data were collected through library research, observation, interview, and documents. The collected data based on conceptual framework and were analyzed accurately and sistematicaly.The result shows that Tor-Tor dance in the funeral ceremony Saur Matua  in batak society at Pematang Siantar up to 2017 has the same movements. All thye movements are the same with the original one. Tor – Tor is a part of ceremony aims to honor the death of old people especially the parents.Keyword: : Persentation Form, Tor-Tor